Strategic management about how to struggle for survival and sustainable development for JA Solar - Chen, Yan (2013)
Solar PV experienced the enormous development in 2010 & 2011, aggressive capacity built-up, especially in China, led to excessive production capacity and supply as well as the intense competition, drove prices falling further and made the margins smaller and smaller for manufacturers in 2012. Established on May 18, 2005, JA Solar is a leading manufacturer of high-performance PV wafers, cells and modules. JA Solar was fast expansion from 2005 to 2011 with 4 global sales offices, 6 factories and 2 R&D centers in China. Since surplus supply, falling price, extreme competition, JA Solar met the challenges. In addition, 29.18% of anti-dumping and anti-subsidy taxes carried out in USA in 2011 for the Chinese PV products exporting to USA market. Moreover, anti-dumping and anti-subsidy extended to Europe… JA Solar is suffering a lot from the heavy pressures and struggles to survive. Firstly, this thesis indicates the data collects of the global PV market situation, including Europe, Asia-Pacific (APAC) region (Except China), the Middle East & North Africa (MENA) region & Africa and PV market situation in China at the end of 2012, briefly presents JA Solar and the bottleneck problems they faced. Secondly, the case study of JA Solar, focus on environmental analysis, including macro-environment, sector, main markets & competitors’ analysis. Thirdly, offers the internal analysis, consisting of the competitive advantage and SWOT analysis. Finally, goes ahead the TOWS analysis and propose the strategic choices for survival and sustainable development for JA Solar.